لترقية قدرة الطلبة على مهارة الكتابة في المدرسة الثانوية الإسلامية الحكومية 3 أتشية غربية " Word Square" تطبيق وسيلة - Hidayatil Muslimah; Sullati Armawi; Ferniza Uun; Zikriati; Jailani; Banta Ali; هداية المسلمة ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2023)
This research Aims to determine the application of the Word square media to improve students' ability in writing skills as well as to determine students' responses to the application of the "Word Square" media in learning writing skills, besides that it also aims to determine the influence of the application of the "Word Square" media in increasing students' ability in writing skills at Madrasah Tsanawiyah Negeri 3 Aceh Barat. This research is experimental research with the type One Group Pre test- Post test Design. The research instruments used in this research were interviews, questionnaires and tests. The research results showed that the response of MTSN 3 West Aceh students to Word Square media was very good. This is shown by the T Test results being greater than the T table value This indicates that applying the “Word Square” method to improve students’ ability to write skills in the Government Islamic Secondary School 3, Western Aceh, is effective, and this indicates that the test result T is greater than the result of the table, which means (2.09<25‚51>2.86) Ho is rejected and Ha is accepted